Correlation between the length of food-related media and eating behavior among students in Quezon City - Macalangcom, Star Raiza J.; Nombres, Allaura D. (College of Home Economics, University of the Philippines Diliman, 2023)
Exposure to Social Networking Sites (SNS), specifically food-related content is among the factors that influence one's dietary habits. This influence may be magnified in the Philippines given that the country is among the most active in online platforms, with social media usage being highest in NCR among Filipinos aged 15-24 years old. There have been attempts to delineate social media into types in terms of length, short-form media (SFM) and long-form media (LFM). Previous studies that explored the effect of social media on eating behavior often focused on the duration of consumption of social media. This study aimed to analyze the correlation between the type of media (in terms of length) consumed and the level of influence of social media on a person’s eating behavior (EB) among undergraduate university students from schools in Quezon City, Philippines. The study was a correlational research that utilized a convenience sample of 104 eligible participants. Data was collected using the Media Consumption and Eating Behavior Questionnaire (MCEBQ), a three-part online questionnaire that included the adapted Scale of Effects of Social Media on Eating Behavior (SESMEB). Results showed that the most consumed media involved food trends, recipe videos, TV reality shows, and food-related advertisements while the least consumed are dietary advice videos. Furthermore, SFM was found to be the preferred type of media for leisure consumption over LFM. The mean SESMEB score of the participants of this study (45.40 ± 12.17) was relatively higher than those of other studies, indicating a relatively higher susceptibility to the influence of social media on EB. SFM and SESMEB had a positive moderate correlation (p=0.597) while LFM and SESMEB had a positive moderate to strong correlation (p=0.606). Based on the correlations, LFM was found to have a higher likelihood in influencing eating behavior over SFM. The study found that the benefits of social media use on EB may be maximized by increasing the amount of entertaining, long-form nutrition material while promoting mindfulness when exposed to media featuring unhealthy eating.